Pilates and mobilization methods in therapy for low back pain among pregnant women - Mączka, Martyna; Sass, Anna (Journal of Education, Health and Sport, 2017)
INTRODUCTION: Bad body posture, insufficient physical activity, excessive body weight gain of pregnant women, with overloads due to pregnancy in their body, results in pain of fatigued muscle. The enlarged uterus with fetus cause the forward shifts of the gravity center which leads to the pelvis forward tilt. This mechanism women compensate by the body posture deflection that leads to lumbar hyperlordosis. In adaptation to the new biomechanical conditions, the iliolumbar and erector spinae muscles are contracted, while the gluteus maximus and abdominal muscles are overstretched. All of these changes are further coused by the increasing levels of relaxin and estrogen hormones in pregnancy, which relax the ligaments and muscles. Muscle weakness and presence of pathological overloads in body leads to lower back pain of the spine. OBJECTIVE: The assessment of lumbar spine pain among women in the third trimester of pregnancy in context of comprehensive therapy of Pilates exercises and lumbar mobilization. MATERIAL AND METHODS: The qualifying interview identified a group of 224 pregnant women with lumbar spine complications. The study was conducted in a targeted manner and all the participants did not have any contraindications from a gynecologist to physical activity during pregnancy. Women who reported sedentary lifestyle, according to pedometer classification, were assigned to a control group (GK) with only a lumbar mobilization intervention. On the other hand, women who were active, were arranged in the Pilates exercise also with lumbar mobilization (GP). Respondents received the Oswestry questionnaire to assess the low back pain. The questionnaire was twice conducted - at 26 Hbd and after the period of interventions in 39 Hbd. In addition, women subjectively assessed the severity of pain sensations in the visual analogue pain scale from 0-10. The obtained data were statistically analyzed. THE RESULTS of the evaluation of lumbar spine pain in 39 Hbd indicate a frequents (p < 0.05) incidences in the control group. In addition, the severity of pain symptoms were higher among the control group than the Pilates group. The intergroup comparison among Pilates and control group showed significant differences in severity of lumbar spine pain due to higher gestational week (between 26 Hbd and 30 Hbd) in both groups. CONCLUSION: The comprehensive therapy inculding the Pilates exercise with lumbar mobilization is more beneficial in pain relief among pregnant women compared to only lumbar mobilization. The effects of the comprehensive therapy inculding the Pilates exercise with lumbar mobilization cause that the intensity of back pain is smaller among pregnant women.